ELASTISITAS KESEMPATAN KERJA BERDASARKAN PRODUKTIVITAS SEKTOR PEREKONOMIAN DI SUMATERA SELATAN - Rosmiyati Chodijah (Department of Development Economics, Universitas Sriwijaya, 2010)
The rate of population growth in Southern Sumatra in 2008 is still quite high at around 1.68%. This is an increase from the year 2000 -2007 with an average growth of 1.36% with a population of 6,486,015 people (UNFPA report and Connecticut to South Sumatra, 2008). Provinces on the island of Sumatra have a different variation from the highest to the lowest. When compared with those provinces in the same year 2008, namely South Sumatra province population growth is not so alarming, but still continue to be vigilant in the development process. Development is essentially a continuous process of change, which is moving towards progress and the repair for the welfare society. Development is not always run smoothly because often needed changes and reforms that can make development more efficient, so it can be felt by every resident. Associated with a number of problems above, should be developed sectors of the economy that can create jobs in large numbers and able to provide adequate income so that each household at least to meet five basic needs. The purpose of this research is to try to examine aspects of labour, especially employment opportunities resulting from economic growth in the period of 2005 to 2010 in the area of South Sumatra province. Based on the above description can be said that the development of Gross Regional Domestic Product (GDP) in South Sumatra region is quite high, but when compared with the national level is still low. Figures are the average growth of 6.1% between theyears2005-2007.Of the three sectors analyzed the growth of GDP from the manufacturing sector is the highest sector, namely by 18.4% followed by the sector A (agriculture) by 5.3% and final service sector of 4.9%.In the development of employment opportunities was A sector that is easy to absorb labour force in many rural and urban development, only 0.03%. Meanwhile, two other sectors namely manufacturing and services sector average growth of 5.25% and 4.63%.Judging from the coefficient of elasticity of employment opportunities for the sector A (agriculture) nearly on the state of a static or inelastic (0.006). For the M sector (manufacturing) employment is still to be said inelastic (0.28), let alone a small number of employment opportunities. Special S sector (services), the coefficient is almost perfectly elastic because of the closer one (0.94). This sector seems to open wide and can quickly accommodate a large work force and quick. Overall, the real problem is Labour's most urgent problem to find a way out when viewed from the situation and current economic conditions in which the global crisis. In the agricultural sector is still a possible expansion of its development with the intensification of agriculture to the expansion of employment opportunities. S sector (services) trade primarily represents the absorption of labour that needs a lot of assistance through infrastructure improvements and expansion of trade, facilitate lending and enhance the relationship of money and goods from urban to rural areas so as to create a strong Keywords: Elasticity, Employment, Opportunity.